Differential Diagnosis of Flank Pain in the Emergency Department - Kadhim A. Al-Hilali, Amer M Al-Taie, Ahmed Sarhan Al-Jobouri, Rafea Qadri Meteab, Zainab Abdul Karim Al-Obaedi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: flank pain is a well-recognized and common complaint among attendants to the emergency department’ worldwide’ and demands careful evaluation and proper management to relief patient’s discomfort Objective: the study was intended to determine the causes of flank pain for patients attending the emergency department Patients and methods: Through a period of seven months (450) patients with flank pain were enrolled in the study in the emergency department. Two hundreds of them were female and (250) were males, their ages ranged from (12-70) years with an average of (38± 8 SD). All of them underwent full evaluation, including detailed history, physical examination and the available investigations, then statistical analysis was done and the results were recorded. Results: The total number of patients in the sample of study was (450), males were (250) and females were (200), with a male to female ratio of (1.25:1). Most patients (nearly 61%) were in the age group (21-40)years . Patients with renal colic due to urolithiasis constituted more than (53%) with male predominance, male to female ratio was (1.7:1). Urinary tract infection made (8.4%) of the total cases of flank pain. Female predominate by (2.8:1), other cases are shown in the accompanying tables. Conclusion: the results showed that most patients with flank pain (61%) were young subjects (21-40) years old. Urolithiasis constituted more than (53%) of the causes of flank pain with a male Predominance by(1.7:1) , while urinary tract infection made more than(8,4%) of the total number of causes , with female predominance (2,8:1). In about (5,6%) of cases no definite cause could be identified Keywords: flank pain, emergency department, urolithiasis, urinary tract infection, Miscellaneous